Water and cell wall contributions to apple mechanical properties. (1st December 2018) - Lahaye, Marc; Bouin, Christopher; Barbacci, Adelin; Le Gall, Sophie; Foucat, Loïc
Highlights: Apple viscoelasticity, water mobility, chemical and histological features were studied. Two types of NMR relaxation analysis assessed water in fresh and plasmolyzed flesh. Water status related with water and solutes contents but not with viscoelasticity. Elastic modulus related with cell wall arabinose and galactose contents. Abstract: Relations between the apple cortex viscoelastic properties, water dynamics, histological, and chemical characteristics were investigated. Water mobility in four apple genotypes was studied by low-field NMR relaxometry prior and after plasmolysis of the cortex tissue. A discrete and a continuous method for decomposing the multi-exponential T 2 curves were implemented and compared. The results show that both methods of relaxation curve decomposition had close ability to discriminate genotypes before and after plasmolysis. Although the sensitivity of T2 relaxometry allowed distinguishing microstructures among genotypes even after cellular fluids were mixed and diffused in plasmolyzed tissues, no relaxation component correlated with apple viscoelasticiy. Galactose and arabinose cell wall content were correlated with the storage modulus (E′) prior and after plasmolysis though the correlation signs were opposite and pointed to a potential key role of pectin RGI side chains in regulating apple texture in turgid tissue.